Antifungal activity of terrestrial Streptomyces rochei strain HF391 against clinical azole -resistant Aspergillus fumigatus - S Hadizadeh; H Forootanfar; GH Shahidi Bonjar; M Falahati Nejad; A Karamy Robati; SA Ayatollahi Mousavi; S Amirporrostami (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Actinomycetes have been discovered as source of antifungal compounds that are currently in clinical use. Invasive aspergillosis (IA) due to Aspergillus fumigatus has been identified as individual drug-resistant Aspergillus spp. to be an emerging pathogen opportunities a global scale. This paper described the antifungal activity of one terrestrial actinomycete against the clinically isolated azole-resistant A. fumigatus. Materials and Methods: Soil samples were collected from various locations of Kerman, Iran. Thereafter, the actinomycetes were isolated using starch-casein-nitrate-agar medium and the most efficient actinomycetes (capable of inhibiting A. fumigatus) were screened using agar block method. In the next step, the selected actinomycete was cultivated in starch-casein- broth medium and the inhibitory activity of the obtained culture broth was evaluated using agar well diffusion method. Results: The selected actinomycete, identified as Streptomyces rochei strain HF391, could suppress the growth of A. fumigatus isolates which was isolated from the clinical samples of patients treated with azoles. This strain showed higher inhibition zones on agar diffusion assay which was more than 15 mm. Conclusion: The obtained results of the present study introduced Streptomyces rochei strain HF391 as terrestrial actinomycete that can inhibit the growth of clinically isolated A. fumigatus.